Ritualisme Ibadah Haji Bawakaraeng Persepsi Masyarakat Lembanna; Studi Kasus Lembanna - Islamy, Muh Fajar; Rahman R, Abd. (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2021)
This study aims to identify people’s perceptions that are directly related to the phenomenon, where the pilgrimage is a complementary worship in Islam. Hajj is one of the pillars of Islam, which is the fifth pillar that must be done for every Muslim, both men and women who are capable and have met the requirements. The implementation of the pilgrimage is to visit the Baitullah (Ka’ba) in Mecca with certain conditions and certain rituals. People who perform hajj are obliged to comply with the provisions. It is different in Lembanna village where some people still believe in the Bawakaraeng pilgrimage ritual. Then it is described in the formulation of the problem, namely: How is the perception of the Lembanna community regarding the ritualism of the Bawakaraeng Hajj? How is the government’s effort in overcoming the ritualism of the Bawakaraeng Hajj? The type of research used is field research, in which this research was conducted in the village of Lembanna. The result of this research is that Haji Bawakaraeng as described is a term or symbol attached to mountain climbing activities during Eid al-Adha. Information from residents at the foot of the mountain said that they did not believe in and did not practice the Bawakaraeng Hajj culture, and this culture was carried out by people outside their environment. Along with this statement they also admitted that they did not agree with the existence of Haji Bawakaraeng. The implications of this research are, Everything must be based on evidence, so that there is no wild perception in society. This research can be an enlightenment or information related to the Hajj Ritual at the Top of Mount Bawakaraeng. If there is information related to rituals in the community and which are suspected of being deviant, don’t judge or blaspheme immediately, it would be better if we have to dig up information first. Changing the community’s paradigm regarding the Hajj ritual at the top of Mount Bawakaraeng. Key Word: Rituals, Hajj, Bawakaraeng